2008
DOI: 10.1016/j.msea.2006.11.181
|View full text |Cite
|
Sign up to set email alerts
|

Properties of fine-grained steels generated by displacive transformation

Abstract: It has been possible in recent times to make large quantities of steels in which the controlling scale is 20 nm or less, i.e., comparable to that of carbon nanotubes. The mechanical properties of such steels are abnormal. For example, in some cases the ductility vanishes as the strength increases, whereas in others the ductility almost entirely consists of uniform plastic strain. Some of the steels also can tolerate large fractions of brittle phases before fracture. These and other aspects of strong, nanostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 27 publications
2
28
0
2
Order By: Relevance
“…it loses percolation (Bhadeshia 2008). Garboczi et al (1995) have modelled the percolation threshold for ellipsoidal objects placed in a matrix.…”
Section: Origin Of Mechanical Propertiesmentioning
confidence: 99%
“…it loses percolation (Bhadeshia 2008). Garboczi et al (1995) have modelled the percolation threshold for ellipsoidal objects placed in a matrix.…”
Section: Origin Of Mechanical Propertiesmentioning
confidence: 99%
“…It has been suggested that with microstructures of the kind considered here, failure in a tensile test occurs when the retained austenite loses continuity [42] and that this percolation threshold is reached when the austenite fraction reaches about 0.1. The fraction of austenite present in the initial microstructure can be calculated from the fact that the bainite reaction, in the absence of cementite precipitation, obeys the incomplete reaction phenomenon.…”
Section: Designmentioning
confidence: 99%
“…Electron diffraction patterns analysis revealed that the microstructure consisted of thin bainitic ferrite plates separated by thin layers of retained austenite. In case of steels this kind of microstructure is called nanobainite [13][14][15], while in ductile iron we can speak of nanoausferrite [6,7]. The average width of ferritic plates was similar for both samples and it was 126 ± 13 nm and 116 ± 7 nm in ADI-1 and ADI-2, respectively.…”
Section: Resultsmentioning
confidence: 96%